1963
DOI: 10.1302/0301-620x.45b3.572
|View full text |Cite
|
Sign up to set email alerts
|

THE VASCULAR CONTRIBUTION TO OSTEOGENESIS V. The Vasculature Supplying the Epiphysial Cartilage in Rachitic Rats

Abstract: 1. It has been shown that in experimental rickets the well known changes in the epiphysial cartilage which so seriously affect growth are accompanied by severe interference with the progress of the metaphysial vessels into the growth cartilage. 2. Further evidence has been found that, by the repeated increase in their number, the cartilage cells occupying the more distal part of the proliferative segment become more and more affected by their remoteness from the epiphysial vessels, which supply the transudate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 6 publications
4
52
0
Order By: Relevance
“…Ironically, the peripheral pattern of excessive hypertrophic chondrocytes observed in classic metaphyseal lesions is similar to the pattern reported in an experimental model of rickets [34]. Trueta and Buhr [34] observed that the proliferation of hypertrophic chondrocytes in rachitic rodents was most excessive in the peripheral growth plate (Fig. 4C), corresponding to the region of greatest compressive forces.…”
Section: Similarities Of the Classic Metaphyseal Lesion With Healing supporting
confidence: 80%
See 1 more Smart Citation
“…Ironically, the peripheral pattern of excessive hypertrophic chondrocytes observed in classic metaphyseal lesions is similar to the pattern reported in an experimental model of rickets [34]. Trueta and Buhr [34] observed that the proliferation of hypertrophic chondrocytes in rachitic rodents was most excessive in the peripheral growth plate (Fig. 4C), corresponding to the region of greatest compressive forces.…”
Section: Similarities Of the Classic Metaphyseal Lesion With Healing supporting
confidence: 80%
“…A diffuse pattern is seen in active stages of rickets because of the inability of vascular invasion and subsequent resorption of terminal chondrocytes in the absence of mineralized matrix. Ironically, the peripheral pattern of excessive hypertrophic chondrocytes observed in classic metaphyseal lesions is similar to the pattern reported in an experimental model of rickets [34]. Trueta and Buhr [34] observed that the proliferation of hypertrophic chondrocytes in rachitic rodents was most excessive in the peripheral growth plate (Fig.…”
Section: Similarities Of the Classic Metaphyseal Lesion With Healing supporting
confidence: 80%
“…The ultimate size and structure of each endochondral bone depend on the coordinated regulation of chondrocyte proliferation, maturation, and hypertrophy in response to multiple extracellular signals (6,7). Interestingly, the blood vessel disruption of the growth plate reduces bone mineralization and the replacement of hypertrophic chondrocytes (8,9), suggesting that bone formation is largely dependent on vascularization.…”
Section: The Regulation Of Hypoxia-inducible Factor-1␣ (Hif-1␣) Durinmentioning
confidence: 99%
“…These studies show that bone morphology abnormalities are generated by mechanical disorders, but conclude that such abnormalities are in no way responsible for deficient growth in the length of long bones (Trueta, , 1961. Frost (1979) contests the validity of this last conclusion on the grounds of possible interference of regional growth phenomena.…”
Section: Introductionmentioning
confidence: 87%
“…Other experiments have verified the vital part played in the growth of bone length by insufficient vascularisation (Showing & Celers, 1965;Troupp, 1961;Trueta, 1958Trueta, , 1961Van der Hoeft et at., 1963;Wo & Mittner, 1937), and hypoxia (Person, 1968), and this is why the resulting inequalities were attributed to the vascular effects of neurological damage.…”
Section: Introductionmentioning
confidence: 92%